Application of Image Media to Increase Student Learning Motivation in Mathematics Lessons in Elementary Schools - Julistin Prilianis Dakhi; Zulvia Misykah; Fahmi Armanda (Outline Journal of Education, 2023)
The purpose of this study is to determine the nature of learning media, to determine the nature of learning motivation, to identify the benefits and effectiveness of image media in the learning process, both for students and teachers, to determine the things to consider in determining a learning media that will be used when teaching. The research methodology used in this journal is a literature review, which aims to analyze and summarize previous studies related to teacher strategies in overcoming cheating behavior in elementary school students. A literature review is an ideal method when the purpose of the study is to understand existing concepts, theories, and research results without conducting experiments or collecting data directly in the field.